ANALISIS HUMAN ERROR PADA OPERATOR ENGINE ROOM PT. ADEI PLANTATION & INDUSTRY DENGAN METODE HUMAN ERROR ASSESMENT AND REDUCTION TECHNIQUE (HEART) - Monica Widiyawati (Fakultas Teknik UMRI, 2020)
PT. Adei Plantation & Industry is a plantation company that operates on plantation and palm oil industries. CPO production of palm oil is needed for consumption, which is run by power stations and for distribution (engine room) involving operators. Since january to june 2020, there is a sudden shutdown in the work of research for the analysis of human errors in the engine room using HEART method. The HEART method is used to evaluate the possibility of human error in all the work and to count the erros in various mays. Data management shows that there are 4 task operators that are common to the plant turbine engines and 6 task forces on the genertor. The highest HEP rating on the turbin engine was 0,6528 with the greatest error potential for task 3, the turbine engine operation. For the highest HEP value on the generator engine is 3,1759 with an error potential in task 5.